BUSINESS PROCESS REENGINEERING PROCUREMENT MATERIALS WAREHOUSE IN PT TELKOM PEKALONGAN - Anpabelt Trah Javala (Media Bina Ilmiah, 2023)
Telkom Pekalongan carries out four main business processes: warehouse material procurement, employee recruitment, Wi-Fi service installation, and Wi-Fi service termination. These four processes are crucial to ensure that material supplies continue to exist and are obtained at low prices, obtain a qualified workforce to fulfill the company's vision and mission, and provide fast and strong internet services for customers. Telkom Pekalongan has established itself as a leading, respected brand in the Indonesian telecommunications industry due to its commitment to continue to grow and develop its business operations. This research is expected to be a learning medium for other companies to learn from Telkom Pekalongan to then understand the importance of business processes and find out how best to implement them. The research method used in this study is mixed methods, bearing in mind that this research uses both qualitative and quantitative methods simultaneously. The findings of this study conclude that Telkom Pekalongan's procurement business process, which is considered very good, experiences problems in the flow of its activities, resulting in inefficient business operations and ineffective business processes. Therefore, activities involving task composition and automation need to be redesigned. Later, after the activity has been redesigned and re-executed, business processes will require lower costs and time, so that business operations can run more efficiently.